AN SCP-BASED ASSESSMENT OF MARKET STRUCTURE AND AIRLINE PERFORMANCE IN POST-PANDEMIC INDONESIA - Nia Sofura; Zenal Asikin; Nur Hasanah (SOSIOEDUKASI, 2026)
This study applies the Structure–Conduct–Performance (SCP) framework to empirically reassess the relationships among market structure, airline conduct, and industry performance in Indonesia’s aviation sector. The analysis integrates descriptive trend analysis to capture post-pandemic industry dynamics and panel data regression techniques to quantitatively evaluate structural and behavioral effects on performance. The findings are intended to provide policy-relevant evidence for enhancing industry competitiveness and long-term resilience. The results indicate that Indonesia’s aviation industry is characterized by a persistent oligopolistic structure, in which market concentration (HHI and CR4) and minimum efficient scale (MES) significantly shape airline behavior and performance. Using fixed-effects panel regression for the 2019–2024 period, the estimates show that higher market concentration and MES have positive and statistically significant effects at the 1–5% level on capacity decisions (ASK) and yield, while airline performance, measured by load factor, remains significantly influenced after controlling for fuel price volatility and GDP growth, providing strong empirical support for the Structure–Conduct–Performance (SCP) framework. This study demonstrates that post-pandemic performance in Indonesia’s aviation industry is primarily driven by market structure and internal operational decisions, particularly capacity management (ASK) and fleet utilization, rather than by pricing strategies, service quality, or short-term macroeconomic conditions.